Comparative assessment of patients' admission to urology departments during and before the COVID-19 pandemic: a retrospective cohort study - Keles, Ahmet; Karakeci, Ahmet; Ozan, Tunc; Yuvanç, Ercan (My University, 2023)
Aim: To determine the diseases that presented to the urology department during the COVID-19 pandemic and for hospital- based comparison with the diseases that presented in the same period of the previous year. Material and Method: In this retrospective follow-up study, patients who were admitted to the tertiary university hospital and secondary state hospital urology departments between April-July 2019 and April-July 2020 were included in the study. We searched the health administrative data using the International Classification of Diseases-10 codes. The number and variety of patients who were admitted to the urology departments in the same months of 2019 and 2020 were compared. Results: In both hospitals, the total number of admissions decreased during the pandemic in 2020 compared to the pre- pandemic year. Also, elective admissions decreased in 2020 compared to the pre-pandemic year (p <0.001). In a significant part of the urological disease group, the decrease in the number of admissions was found to be higher for the second-level center than for the tertiary center hospital. Conclusion: We documented that uro-oncology outpatient admissions could continue during the COVID-19 pandemic in a university hospital- not primarily served as a pandemic hospital- by taking preventive measures and prioritizing healthcare personnel and patient safety.
Keywords: COVID-19; pandemics; urologic diseases